If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(6p + 3) + -2(2 + -17p) = 3(9 + 5p) Reorder the terms: -3(3 + 6p) + -2(2 + -17p) = 3(9 + 5p) (3 * -3 + 6p * -3) + -2(2 + -17p) = 3(9 + 5p) (-9 + -18p) + -2(2 + -17p) = 3(9 + 5p) -9 + -18p + (2 * -2 + -17p * -2) = 3(9 + 5p) -9 + -18p + (-4 + 34p) = 3(9 + 5p) Reorder the terms: -9 + -4 + -18p + 34p = 3(9 + 5p) Combine like terms: -9 + -4 = -13 -13 + -18p + 34p = 3(9 + 5p) Combine like terms: -18p + 34p = 16p -13 + 16p = 3(9 + 5p) -13 + 16p = (9 * 3 + 5p * 3) -13 + 16p = (27 + 15p) Solving -13 + 16p = 27 + 15p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-15p' to each side of the equation. -13 + 16p + -15p = 27 + 15p + -15p Combine like terms: 16p + -15p = 1p -13 + 1p = 27 + 15p + -15p Combine like terms: 15p + -15p = 0 -13 + 1p = 27 + 0 -13 + 1p = 27 Add '13' to each side of the equation. -13 + 13 + 1p = 27 + 13 Combine like terms: -13 + 13 = 0 0 + 1p = 27 + 13 1p = 27 + 13 Combine like terms: 27 + 13 = 40 1p = 40 Divide each side by '1'. p = 40 Simplifying p = 40
| (1/8X)-(5/6)=X-(3/4) | | 5a+a+5= | | n+4+4n=11 | | -5a+8-6a=35 | | -6(8+3k)=-16 | | Kx=my+mx | | cos(x)-.5sin(x)=.3 | | (6x-17)/2x | | Kx=my-my | | Y=128-x^2 | | 2(5-x)+3=-15-2 | | 23=-6+4(d-5) | | -2x-4=11 | | 20x-3x-2x+(-5)-19x=-9 | | 2x-10y+2=0 | | X-38=10 | | 3(4x+3)=2x-5(3x-x)+2 | | 18m^2+63=69m | | 6y+7x=29.30 | | x+12.4=-6.6 | | X^4+8X^3+12x^2-24x+3=0 | | -1-3b=7 | | -0.2222222222222222X-0.25=-1.5-0.1666666666666667X | | -29=-5f-6f | | 0.2x+1.98+3.02=4.14 | | 5r-7-3r=16 | | 3p^2+7=22p | | 2s-6s=24 | | 15x^4+24x^3-8x=0 | | -(2/9X)-(1/4)=-(3/2)-(1/6X) | | -6(1+9x)=33 | | 2p+15q=8 |